International Innovation Indicators - Dermot P. Coates; Keith Fitzgerald (National Competitiveness and Productivity Council (NCPC), 2023)
Ireland's ranking in the Global Innovation Index stood at 23rd in 2022, with a significantly stronger performance under innovation outputs (19th) compared to innovation inputs (25th). Ireland's ranking has deteriorated in recent years. Ireland last reached the top 10 in 2018. While Ireland was regarded as a 'Strong Innovator' in the European Innovation Scoreboard 2023, our lead over lower ranking countries is shrinking, while the higher ranking "Innovation Leaders" are increasing their lead. Dublin ranks 18th in the European Digital Social Innovation Index, with a strong performance under 'Skills'. Composite indices of innovation are valuable tools to assess and benchmark Ireland's performance versus international competitors; however, these indices should be interpreted with caution and must be understood in the broader macroeconomic and policy context. The use of GDP to denominate or scale indicator values risks misrepresenting Ireland's performance.
Keywords: 330